IoT Phase Loss Monitoring System for Low Voltage Panels: Sistem Pemantauan Kehilangan Fase IoT untuk Panel Tegangan Rendah - Ananda Putra Suwarno; Syamsudduha Syahrorini Arifianto; Jamaaludin Suwarno (Indonesian Journal of Innovation Studies, 2025)
General Background Electrical distribution systems require reliable monitoring to prevent damage and service disruption caused by voltage anomalies. Specific Background Phase loss in low-voltage connection panels can lead to equipment damage and delayed handling due to conventional reporting systems. Knowledge Gap Existing complaint systems relying on SMS technology are inefficient and lack real-time monitoring capabilities. Aims This study aims to design and develop an Internet of Things-based phase loss monitoring and complaint system for low-voltage panels. Results The system utilizes NodeMCU ESP32, PZEM-004T sensors, GPS modules, and Telegram integration to monitor voltage conditions and send real-time notifications. Testing shows accurate voltage readings with an average accuracy of 98% and data transmission delay of 1.54 seconds. The system successfully detects abnormal voltage conditions below 220V, above 240V, and zero voltage while providing location information. Novelty The integration of real-time monitoring, automatic notification, and location tracking in a single IoT system provides a comprehensive solution for electrical disturbance handling. Implications This system supports faster response by technicians and improves operational efficiency in managing electrical distribution disturbances. Keywords: IoT Monitoring, Phase Loss, Low Voltage Panel, ESP32, PZEM-004T Key Findings Highlights Voltage anomaly detection operates with high measurement precision Notification delivery shows consistent low latency performance Location tracking enables rapid identification of disturbance points